2014
DOI: 10.5330/2156-759x-18.1.136
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Mental Health Professionals' Bullying Assessment Practices: A Call for Evidence-Based Bullying Assessment Guidelines

Abstract: A sample of 483 school-based mental health professionals completed a survey about the training they have received related to conducting bullying assessments in schools, competence in conducting an assessment of bullying, and the bullying assessment methods they used. Results indicate that school counselors were usually informed about incidents of bullying more frequently than school psychologists. Whereas the majority of school-based mental health professionals surveyed reported some level of competence in usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Based on the results, it was apparent that our sample had not experienced as many social life disruptions throughout elementary and middle school transitions as educators had feared. Additionally, our results appeared to support those findings delivered by other special education researchers related to bullying (Blake et al, 2014), suggesting that youths living with special needs may have resilient qualities that help them endure transitions between grade levels.…”
Section: Resultssupporting
confidence: 87%
“…Based on the results, it was apparent that our sample had not experienced as many social life disruptions throughout elementary and middle school transitions as educators had feared. Additionally, our results appeared to support those findings delivered by other special education researchers related to bullying (Blake et al, 2014), suggesting that youths living with special needs may have resilient qualities that help them endure transitions between grade levels.…”
Section: Resultssupporting
confidence: 87%
“…Participants were either certain an adult would enact further bullying, or that the adults were not trained well enough to respond appropriately to bias‐based bullying situations. Consistent with the research, results suggest it will be crucial to focus on bolstering school adults’ abilities to assess and respond appropriately to bias‐based bullying in schools (Blake, Banks, Patience, & Lund, ). In addition to perceived adult ambiguity, participants felt that there are not enough distributed resources about bias‐based bullying in the schools.…”
Section: Discussionsupporting
confidence: 59%
“…Goodman-Scott, Doyle, and Brott (2013) found that the school counselor's role in these activities (i.e., conducting lessons) was crucial in the success of a bullying prevention program. In view of prior research that shows school counselors often hear reports of bullying incidents (Blake et al, 2014) and are more likely to intervene than teachers (Bauman, Note. Response options: school counselor perceives no responsibility for this area, school counselor perceives their principal thinking that the school counselor has no responsibility for this area, school counselor perceives responsibility for assisting with this area, school counselor perceives the principal thinking that the school counselor should have responsibility for assisting with this area, school counselor perceives equal responsibility for this area, school counselor perceives the principal thinking that the school counselor has equal responsibility for this area, school counselor perceives primary responsibility for this area, and school counselor perceives the principal thinking that the school counselor has primary responsibility for this area.…”
Section: Discussionmentioning
confidence: 99%
“…Students who commit acts of bullying also are often among the most popular (Rodkin, Ryan, Jamison, & Wilson, 2013). Blake, Banks, Patience, and Lund (2014) used the term bully-victims to describe students who both bully others and who are bullied. These students appear to exhibit the highest degree of psychological maladjustment (Blake et al, 2014;Dukes, Stein, & Zane, 2009).…”
Section: Defining Bullying and Its Consequencesmentioning
confidence: 99%